ENVIRONMENTAL INCIDENTS, PEMBERITAAN MEDIA DAN PRAKTIK PENGUNGKAPAN LINGKUNGAN (ENVIRONMENTAL DISCLOSURES) : STUDI PADA SUSTAINABILITY REPORT ASIA PULP AND PAPER Co., Ltd. - Kurnia Putri Pratiwi; Anis Chariri (Diponegoro Journal of Accounting, 2013)
The aim of this research is to answer, understand and analyze why and how environmental incident has an impact on APP environmental disclosure practices in sustainability reporting associated with the media attention. Ontologically, this study is build on a belief that environmental disclosure in sustainability report is a communication medium that arise because of public pressures through mass media related to environmental incidents. This research was conducted by employing semiotic and content analyses. By employing those analyses, the findings show that sustainability reporting used by a company as a part of its responsibility to the environment which was affected by the incidents. The finding also suggest that APP environmental disclosure practices in sustainability report was associated with the public pressures as measured by media attention coverage towards the incidents.